Book Review: *The Psychology of Social Influence: Modes and Modalities of Shifting Common Sense* - Hak-Soo Kim (Asian Journal for Public Opinion Research)
This is a book review of Gordon Sammut and Martin W. Bauer's (2021). _The Psychology of Social Influence: Modes and Modalities of Shifting Common Sense_. Cambridge University Press. No one should start research without exposure to the research covered in the book.